The lacemaker and the princess - Bradley, Kimberly Brubaker (Margaret K. McElderry Books, 2007)
In 1788, eleven-year-old Isabelle, living with her lacemaker grandmother and mother near the palace of Versailles, becomes close friends with Marie Antoinette's daughter, Princess Therese, and finds their relationship complicated not only by their different social class but by the growing political unrest and resentment of the French people.